Speculative bubble in IPOs: evidence from Malaysian Fixed-Price IPOs - Othrnan Yong (Penerbit Universiti Kebangsaan Malaysia, 2014)
This paper examines the issue of speculative bubble in the pricing of Malaysian IPOs. In a fixed-price offering, one would expect the post-listing price movement to behave in accordance to a speculative bubble, where the IPO's price is pushed up high above its true value, and later stabilizes as the bubble bursts, especially when there is no stabilization activity taking place. One would also expect that this speculative bubble will be predominant in IPOs that have high pre-listing investor demand, and in IPOs that are categorized as hot issues. In general, the Malaysian fixed-price IPOs do not exhibit the characteristics of speculative bubble. With high demand POs and hot issues IPOs, there is a significant jump in price during the first day of trading, but later the prices starts to drop gradually from their peak to their "true" value; there is no sudden drop in price as in the case of a speculative bubble. Prices seem to stabilize almost immediately in the aftermarket.